Health Impact Assesment: Hints and Cautions from Critical Epidemiology - Breilh Paz y Miño, Jaime Eduardo (Harvard School of Public Health. Conference on Health Impact Assessment and Human Rigths, 2013)
Under the format of this conference, to convey the possibilities for health impact assessment of Latin American Critical Epidemiology, sometimes referred to under the tautological designation of “social epidemiology”, I will try to sum up in the next few minutes some reflections based on them.
Keywords: EPIDEMIOLOGÍA CRÍTICA; EPISTEMOLOGÍA; CONGRESOS Y CONFERENCIAS